A Study of Level of Aspiration among Secondary School Students of Bellary District: A Comparative Study of Aspirations among Secondary School Students in Urban and Rural Areas of Bellary District (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Educational aspiration is an essential variable in predicting achievement and may be seen as an element in academic achievement motivation, focusing as they do on the strong desire for success and the development of goals to succeed in particular educational areas or to gain a particular grade. There are different theoretical perspectives on the explanation of educational aspiration and its consequence for the future behavior.. This article is intended to investigate the level of aspirations among Secondary School Students of Bellary District. The results show that both boys and girls students from urban area, rural area, and whose parents are having college level education have better level of aspiration.